Feynman path integrals in quantum mechanics and statistical physics - Fai, Lukong Cornelius (Boca Raton : CRC Press, 2021)
This book provides an ideal introduction to the use of Feynman path integrals in the fields of quantum mechanics and statistical physics. It is written for graduate students and researchers in physics, mathematical physics, applied mathematics as well as chemistry. The material is presented in an accessible manner for readers with little knowledge of quantum mechanics and no prior exposure to path integrals. It begins with elementary concepts and a review of quantum mechanics that gradually builds the framework for the Feynman path integrals and how they are applied to problems in quantum mechanics and statistical physics. Problem sets throughout the book allow readers to test their understanding and reinforce the explanations of the theory in real situations. Features: Comprehensive and rigorous yet, presents an easy-to-understand approach. Applicable to a wide range of disciplines. Accessible to those with little, or basic, mathematical understanding.
OCLC-licensed vendor bibliographic record.
Keywords: Feynman integrals; Quantum theory; Statistical physics; SCIENCE / Mathematical Physics; SCIENCE / Mechanics / General; MATHEMATICS / General